Pengaruh Budaya Organisasi, Disiplin Kerja, Dan Kompetensi Terhadap Kinerja Guru Melalui Motivasi - Rahayu, Sucik; Wangsanata , Susana Aditiya; Rosari , Dwi Vianita; Nikhla, Anisa Muhimmatun; Putri, Amanda Alivia (Indonesian Journal of Education and Learning, 2024)
The aim of this research is to show and test the influence of organizational culture, work discipline and competency on teacher performance through motivation at MA Sunniyyah Selo Grobogan. This research is quantitative. The results of the T test show that the organizational culture of MA Sunniyyah Selo in Tawangharjo District, Grobogan Regency has a positive and significant impact on teacher motivation, Work discipline has a positive and insignificant impact on the desires of MA Sunniyyah Selo teachers in Tawangharjo District, Grobogan Regency, Competence and work discipline of MA teachers Sunniyyah Selo. Meanwhile, the results of the F test of equality show that organizational culture, work discipline and skills have a positive and significant effect on the motivation of MA Sunniyyah Selo teachers, Tawangharjo District, Grobogan Regency. The F test for equation 1 also shows that organizational culture, work discipline and skills have a positive and significant effect on the performance of MA Sunniyyah Selo teachers, Tawangharjo District, Grobogan Regency. Apart from that, the results of the determination test show that with a total R square value of 0.6222, the intervention variables of organizational culture, work discipline, competence and motivation contribute 62.22% of the performance variables of MA Sunniyyah Selo teachers, Tawangharjo District, Grobogan Regency. Other variables, such as communication, work environment, training, and other variables not included in the research model amounted to 37.78%. The results of the path analysis show that organizational culture has a greater impact on performance than motivation-oriented communication. The influence of work discipline on performance is more influenced by motivation than communication that is motivated by motivation. The influence of competence on performance is more influenced by motivation than competency on performance. . Organizational culture influences the performance of MA Sunniyyah Selo teachers, Tawangharjo District, Grobogan Regency.